2016
DOI: 10.1186/s13054-016-1496-x
|View full text |Cite
|
Sign up to set email alerts
|

The vulnerable microcirculation in the critically ill pediatric patient

Abstract: In neonates, cardiovascular system development does not stop after the transition from intra-uterine to extra-uterine life and is not limited to the macrocirculation. The microcirculation (MC), which is essential for oxygen, nutrient, and drug delivery to tissues and cells, also develops. Developmental changes in the microcirculatory structure continue to occur during the initial weeks of life in healthy neonates. The physiologic hallmarks of neonates and developing children make them particularly vulnerable d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 117 publications
(177 reference statements)
0
15
0
Order By: Relevance
“…This excessive O 2 release has been shown to cause oxidative stress to the tissues through the production of toxic reactive oxygen species (ROS) and to induce detrimental microvascular shunting mechanisms that may inappropriately impair tissue perfusion. Delivery of excess O 2 in the setting of shock is a frequent contributor to microcirculatory shunting with significant clinical consequences [ 31 ]. While vascular indices can frequently be normalized within the macrocirculation in the setting of shock, tissue perfusion can nevertheless be compromised because of shunting at the microcirculatory level.…”
Section: Discussionmentioning
confidence: 99%
“…This excessive O 2 release has been shown to cause oxidative stress to the tissues through the production of toxic reactive oxygen species (ROS) and to induce detrimental microvascular shunting mechanisms that may inappropriately impair tissue perfusion. Delivery of excess O 2 in the setting of shock is a frequent contributor to microcirculatory shunting with significant clinical consequences [ 31 ]. While vascular indices can frequently be normalized within the macrocirculation in the setting of shock, tissue perfusion can nevertheless be compromised because of shunting at the microcirculatory level.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported associations between poor outcomes and EA in critically ill children ( 63 67 ). Likewise, the link between childhood obesity and poor outcomes in critical illness is well-established ( 68 71 ).…”
Section: Obesity-associated Endothelial Activationmentioning
confidence: 99%
“…16 The term hemodynamic coherence refers to jointly functioning or dysfunctional macrovascular and microvascular blood flow (eg, normal blood pressure and normal CRT or low blood pressure and prolonged CRT). 17 In critically ill children, hemodynamic coherence may break down, and macrovascular parameters may not reflect microvascular flow at the cellular level, classically illustrated by the low blood pressure and flash CRT state of toxic shock syndrome. Arteriolar EC dysfunction results in pathologic vasoregulation and maldistribution of blood flow manifest as flash or prolonged capillary refill.…”
Section: Endothelial Dysfunction and Blood Flowmentioning
confidence: 99%